Effect of Heat Input on Microstructure, Friction and Wear Properties of Fe-Cr-B-C Coating on AISI 1020 Surface Coated by PTA Method - Gürgenç, Turan; Özel, Cihan (Fırat University, 2017)
In this study, low carbon steel AISI 1020 surface was coated in different heat inputs with (%-wt.) 70FeCrC-30FeB ferro alloy powder mixture by using plasma transferred arc (PTA) welding method. The microstructure of the coating layers were investigated by using optical microscope (OM), scanning electron microscope (SEM),     X-ray diffraction (XRD) and energy dispersive X-ray (EDS). The dry sliding wear and friction properties were determined using a block-on-disc type wear test device. Wear tests were performed at 19.62 N, 39.24 N, 58.86 N load and the sliding distance of 900 m. The results were show that coated samples were consisted of mostly M7C3 (M=Cr, Fe) carbide, (Cr, Fe)B, FeB and Fe2B boride. It was seen that the dendrites were growth with increasing heat input. The highest average microhardness value was measured 1096 HV on sample coated with low heat input. It was determined that the sample with the highest wear resistance was the sample coated by the low heat input.